Strategi Digital Marketing Pada Instagram Wedding Organizer @Djavawedding - Hendra Putri, Aulia Lestari; Arindawati, Weni A.; Nurkinan, Nurkinan (Peneliti.net, 2023)
Business development in the service sector is currently experiencing a lot of improvement, especially in Indonesia. One of them is the Wedding Organizer. Wedding Organizer is a business that operates in the service business which focuses on wedding services. Djava Wedding is one of the Wedding Organizers in Karawang Regency which has 6,472 Instagram followers. This is the reason Instagram is used as an online promotional medium. Digital marketing using social media is an interesting choice, especially using Instagram media. This research uses qualitative methods and a descriptive approach. The theory used is the AISAS Theory (Attention, Interest, Search, Action, Share). The aim of this research is to find out the implementation of digital marketing strategies on the @djavaawedding Instagram account and how to manage the @djavawedding Instagram account. The results of the research on the @djavawedding account at least fulfill the elements of attention, interest and search from Instagram users. Utilization of Instagram features is also maximized to produce appropriate responses from both the admin and followers of the @djavawedding account.